Isolation and identification of a novel porcine-related recombinant mammalian orthoreovirus type 3 strain from cattle in Guangxi Province, China - Luo, Yuhang; Wang, Yanglin; Tang, Wenfei; Wang, Cui; Liu, Huanghao; Wang, Xiaoling; Xie, Jiang; Wang, Jie; Ouyang, Kang; Chen, Ying; Wei, Zuzhang; Qin, Yifeng; et al. (Frontiers in Microbiology, 2024)
The Mammalian orthoreovirus (MRV) infects various mammals, including humans, and is linked to gastrointestinal, respiratory, and neurological diseases. A recent outbreak in Liuzhou, Guangxi, China, led to the isolation of a new MRV strain, GXLZ2301, from fecal samples. This strain replicates in multiple cell lines and forms lattice-like structures. Infected cells exhibit single-cell death and syncytia formation. The virus's titers peaked at 10 7.2 TCID50/0.1 mL in PK-15 and BHK cells, with the lowest at 10 3.88 TCID50/0.1 mL in A549 cells. Electron microscopy showed no envelope with a diameter of about 70 nm. Genetic analysis revealed GXLZ2301 as a recombinant strain with gene segments from humans, cows, and pigs, similar to type 3 MRV strains from Italy (2015-2016). Pathogenicity tests indicated that while the bovine MRV strain did not cause clinical symptoms in mice, it caused significant damage to the gut, lungs, liver, kidneys, and brain. The emergence of this MRV strain may pose a threat to the health of animals and humans, and it is recommended that its epidemiology and recombination be closely monitored.